Socio-economic impact of the COVID-19 pandemic on Overseas Filipino Workers and their left-behind families: a scoping review - Gomez-Magdaraog, Kristel May; Burton-Jeangros, Claudine; Jackson, Yves (Frontiers in Political Science, 2024)
Overseas Filipino Workers (OFWs) are considered bagong bayani, or modern-day heroes, as their remittances have a positive long-term impact on the Philippines economy.The Philippines ranked 10 th worldwide in terms of net emigration from 2010 to 2020. The deployment of OFWs declined during the pandemic, and this was estimated to have adverse effects on remittances. As a migrant-sending country, the Philippine government had to deal with the mass of unemployed OFWs stranded in their host countries and organize large-scale repatriation of OFWs. This scoping review aims to assess the existing literature, identify research gaps, and propose future research directions concerning the socio-economic impact of the COVID-19 pandemic on OFWs and their left-behind families. The results indicate that the impact of the pandemic on OFWs was not uniform. It is evident that OFWs in precarious situations beforehand have become even more vulnerable. The loss of their source of income in the host country and the restrictions on international mobility during the pandemic had significant detrimental effects on their well-being and their families left behind, regardless of their income level or type of job. Upon returning to their home country, they often experienced anxiety, depression, discrimination, and difficulty in finding a job. Overall, this scoping review highlights the urgent need for greater recognition and protection of OFWs in times of crisis. It is crucial to address the systemic issues that contribute to their vulnerability and to ensure that they receive adequate support and protection in host countries and the Philippines.